2014
DOI: 10.3892/ol.2014.2730
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA PVT1 is associated with tumor progression and predicts recurrence in hepatocellular carcinoma patients

Abstract: PVT1, which maps to chromosome 8q24, is a copy number amplification-associated long non-coding RNA. Overexpression of PVT1 is a powerful predictor of tumor progression and patient survival in a diverse range of cancer types. However, the association between PVT1 and hepatocellular carcinoma (HCC) remains unclear. The aim of the present study was to examine the expression pattern of PVT1, and its clinical significance in HCC. Between 2003 and 2012, reverse transcription-quantitative polymerase chain reaction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 32 publications
6
107
0
2
Order By: Relevance
“…In several cancers, PVT1 is found to be upregulated in cancer tissues than in adjacent normal tissues, and acts to induce cell proliferation and suppress apoptosis (21)(22)(23). In addition, overexpression of PVT1 is involved in cancer resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In several cancers, PVT1 is found to be upregulated in cancer tissues than in adjacent normal tissues, and acts to induce cell proliferation and suppress apoptosis (21)(22)(23). In addition, overexpression of PVT1 is involved in cancer resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) (i.e., evolutionarily conserved non-coding RNAs that are longer than 200 nucleotides and are not translated into a protein) [5,6] exert regulatory functions in cellular processes, such as proliferation, apoptosis, tumorigenesis, and cancer progression and metastasis [7][8][9] . Recently, several studies of lncRNAs have indicated that they may play a pivotal role during the initiation and progression of human cancers, including cervical cancer [10][11][12][13] . In the present study, the researchers focused on the lncRNA PVT-1.…”
Section: Introductionmentioning
confidence: 99%
“…Amplification of 8q24 is one of the most frequent events in a wide variety of malignant diseases. Indeed, PVT-1 generates antiapoptotic activity in human cancers, and overexpression of PVT-1 is a powerful predictor of tumor progression and patient survival in hepatocellular carcinoma [10] ; non-small cell lung cancer [18] ; and colorectal [12] ,ovarian, and breast cancers [15] . Furthermore, PVT-1 has been investigated as a new regulator of various biological processes, such as cell growth, apoptosis, mobility, and invasion [12,15] .…”
Section: Introductionmentioning
confidence: 99%
“…Kaneko et al demonstrated that MEG3 interacted with PRC2 mainly through the RBR of JARID2 and MEG3 acts in trans on PRC2 and JARID2 by facilitating their recruitment to a subset of target genes [40]. PVT1 silenced P15/P16 in in trans by recruiting EZH2 [41]. The upregulated EZH2 enforces hepatocellular carcinoma cell proliferation (Figure 2a).…”
Section: Interaction With Histone-modifying Complexesmentioning
confidence: 99%